What HR Managers need to know about Circadian Clocks? - Mohiya, Mohamed S. (International Journal of Psychosocial Rehabilitation, 2020)
The alteration of day and night, and changes in seasons has been instrumental in bringing out certain peculiar cyclic changes in the habits and behaviours of all living organisms. These cycles of the body known as “circadian cycles” help organisms to (re)act to varying stimuli in their internal and external environments, resulting in certain behavioural rhythms. Subsequent to the Industrial Revolution, humans started adapting the so called 24 x 7 type of life style. With competition raising its amorphous head due to liberalisation and globalisation, the lifestyles of humans have undergone a paradigm shift. This lifestyle often results in acting contrary to the circadian rhythms that have been set since generations, leading to various complications of astronomical proportions that have been unheard of in earlier generations. This work reviews the accumulated literature about circadian system and strives to find its applications in the present wellness programs. It also discusses the implications for HR Managers.Key words-- , circadian clock, circadian cycle, circadian rhyme, Circadian Rhyme Disruption